The clocks - Christie, Agatha, 1890-1976. (New York, N.Y. : HarperPaperbacks, 1991)
Belgian detective Hercule Poirot must race the clock to solve a murder before another death occurs.
Young Adult
Keywords: Crime -- Fiction; Murder -- Fiction; Poirot, Hercule (Fictitious character) -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction; Detective and mystery stories